2000
DOI: 10.1258/0022215001904284
|View full text |Cite
|
Sign up to set email alerts
|

Optimum imaging for inverted papilloma

Abstract: Inverted papilloma is the most common benign tumour of the nose and paranasal sinuses, and usually arises in the lateral wall of the nasal cavity and the middle meatus. The diagnosis is suggested on computed tomography (CT) when there is a mass continuous from the middle meatus into the adjacent maxillary antrum, through an expanded maxillary ostium. The mass may contain areas of high density or calcification, and there may be sclerosis of the wall of the affected sinus. The main advantage of magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 6 publications
0
60
0
2
Order By: Relevance
“…Regarding the preoperative imaging studies, Savy et al reported that it was very difficult to distinguish SCC associated with IP from IP on CT [17]. To differentiate SCCs and IPs, a well-known criterion is the conventional MRI finding of CCP, which was described as a band-like appearance of high and low intensity on T2WI or CE-T1WI.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the preoperative imaging studies, Savy et al reported that it was very difficult to distinguish SCC associated with IP from IP on CT [17]. To differentiate SCCs and IPs, a well-known criterion is the conventional MRI finding of CCP, which was described as a band-like appearance of high and low intensity on T2WI or CE-T1WI.…”
Section: Discussionmentioning
confidence: 99%
“…An inverted papilloma on CT scan typically presents as a mass arising from the middle meatus and extending into both the maxillary antrum and nasal cavity. The mass is also seen to enhance heterogeneously, shows areas of high density or calcification and bony deformity and sclerosis of the wall of affected sinus [17,18] (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…However, with the progress in the endonasal endoscopic surgical technique, there has been much debate regarding possible benefits of such surgical approach over traditional ones such as lateral rhinodomy, degloving and sublabial approach [9]. Nasal cavity and paranasal sinuses CT scan suggest IP when there is an image of soft tissue present from the middle meatus all the way to the adjacent maxillary antrum, through an enlarged maxillary ostium, as the one seen in our patient.…”
Section: Discussionmentioning
confidence: 55%